2017
DOI: 10.1111/jocd.12366
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress and psychiatric morbidity in patients with facial acne

Abstract: Our results indicate that the high levels of anxiety and depression in patients with facial acne were not related to oxidative stress. Anxiety was more common than depression and was directly related to QoL impairment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 23 publications
2
27
0
1
Order By: Relevance
“…In oxidative stress, the balance between antioxidant defense mechanism and free radical formation is disturbed and endothelial dysfunction occurs 15 . Acne patients not only have local tissue damage but are also under systemic oxidative stress 16 . Recent studies have shown that oxidative stress is important in the progression of acne as well as the etiopathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…In oxidative stress, the balance between antioxidant defense mechanism and free radical formation is disturbed and endothelial dysfunction occurs 15 . Acne patients not only have local tissue damage but are also under systemic oxidative stress 16 . Recent studies have shown that oxidative stress is important in the progression of acne as well as the etiopathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…While some authors found significant relationship between acne severity and quality of life; some of them did not report any significant relationship [10,[16][17][18][22][23][24][25][26]. The differences in the findings of various studies higlight the social, behavioral and cultural factors, differences in population characteristics and individual perception.…”
Section: Discussionmentioning
confidence: 99%
“…In the other hand Kouotou et al in Cameroon [13] showed that the severity of acne influences the occurrence of anxiety since they found a positive correlation between the ECLA and GAD-7 scores. Awad et al in Egypt [22], Lukaviciute et al in Lithuania [19],Gül et al [17] and Öztürk et al in Turkey [7] also found positive correlation between severity of acne and anxiety, hence the importance of taking in charge patient on psychological plan no matter the severity of their acne.…”
Section: Discussionmentioning
confidence: 99%